2012
DOI: 10.1111/nmo.12029
|View full text |Cite
|
Sign up to set email alerts
|

Na+/Ca2+ exchanger 2‐heterozygote knockout mice display decreased acetylcholine release and altered colonic motility in vivo

Abstract: In this study, we demonstrate that NCX2 regulates colonic motility by altering ACh release onto the myenteric neurons of the distal colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…On the other hand, the magnitudes of EFS-induced relaxation were greater in Double HET (Fig. 2C) compared with NCX1 HET (15). There is a significant change between EFS-induced relaxation in Double HET and that in NCX1 HET.…”
Section: +mentioning
confidence: 72%
See 4 more Smart Citations
“…On the other hand, the magnitudes of EFS-induced relaxation were greater in Double HET (Fig. 2C) compared with NCX1 HET (15). There is a significant change between EFS-induced relaxation in Double HET and that in NCX1 HET.…”
Section: +mentioning
confidence: 72%
“…5B). In contrast, NCX2 HET exhibited magnitudes of NOR-1-induced relaxation similar to those of WT (15). We have already demonstrated that NCX2 HET showed enhanced amplitudes of EFS-induced relaxation by decreasing ACh release (15).…”
Section: +mentioning
confidence: 90%
See 3 more Smart Citations